A Survey of Common Payment Methods and Their Determinants in Dental Clinics, in Tehran, 2018 - Emrani, Reza; Sargeran, Katayoun; Grytten, Justein; Hessari, Hossein (European Journal of Dentistry, 2019)
Objective It is believed that the payment method to dentists may affect their treatment decisions. Although payment systems may enhance job satisfaction, reduce the costs, and make better treatment decisions, there is little information about how to achieve these objectives. The aim of the present study was to survey the payment methods and the related factors in dental clinics of Tehran.Materials and Methods Using the latest list published by the Iranian Ministry of Health, we visited all dental clinics located in Tehran, and used a checklist to collect the data of the type of management, geographical location of the clinic in Tehran, payment method and its amount, history of payment method changes in the last decade, relationship between the amount of payment and the position of technical supervisor dentist, any difference in the amount of payment to male and female dentists and to young and experienced dentists. Then, the relationship between the amount of payment and the above-mentioned variables was investigated.Results The governmental sector tends to use fixed salary methods and the private sector usually uses the fee-for-service (FFS) method. Geographical location, type of management, date of establishment, and having the position of technical supervisor dentist had a significant relationship with the amount of payment. The dentist’s gender and years of experience did not have any relationship with the amount of payment.Conclusion According to the results of the present study, the method and amount of payment to dentists were related to the date of clinic establishment, having the position of technical supervisor dentist, and geographical location of the clinic. These factors could be considered as the main elements in balancing costs in clinics and improving job satisfaction among dentists.
Keywords: fixed salary; fee-for-service; payment method; dentistry